2018
DOI: 10.1038/s41523-018-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of post-mastectomy breast cancer recurrence

Abstract: Breast cancer (BC) adjuvant therapy after mastectomy in the setting of 1–3 positive lymph nodes has been controversial. This retrospective Translational Breast Cancer Research Consortium study evaluated molecular aberrations in primary cancers associated with locoregional recurrence (LRR) or distant metastasis (DM) compared to non-recurrent controls. We identified 115 HER2 negative, therapy naïve, T 1–3 and N 0-1 BC patients treated with mastectomy but no post-mastectomy radiotherapy. This included 32 LRR, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Notably, 1 patient in the matched series had a complete mismatch of genomic alterations, with a match of polymorphisms (not shown) confirming the same donor. We had reported such a case in a prior breast cancer study as well (23). Such cases emphasize that patients with DM could have another primary (same tumor type or other), emphasizing importance of pathologic confirmation of metastatic disease.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Notably, 1 patient in the matched series had a complete mismatch of genomic alterations, with a match of polymorphisms (not shown) confirming the same donor. We had reported such a case in a prior breast cancer study as well (23). Such cases emphasize that patients with DM could have another primary (same tumor type or other), emphasizing importance of pathologic confirmation of metastatic disease.…”
Section: Discussionmentioning
confidence: 74%
“…We had identified NF1 loss in patients with both HR þ MBC and TNBC, and found that NF1 deletions noted on NGS on the T200 platform are indeed lost on SNP arrays. We had also reported NF1 as a gene of interest in a multicenter study of patients with breast cancer who had modified radical mastectomy for clinical node positive disease with 1-3 positive nodes (23). DNA analysis on primary tumors of patients who developed a LRR or DM versus patients who did not recur identified significantly more NF1 mutations in patients with LRR or DM, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…HOXB9v was commonly detected from clinical breast cancer samples (Figure 3(a)), regardless of their hormone receptor and HER2 status. However, HOXB9v was not detected in normal mammary gland samples (Figure 3(b) us, to further confirm the presence of HOXB9v in human breast cancer samples, we reanalyzed a publicly available breast cancer RNA sequence data set (GSE119937) [18] and mapped the reads onto the HOXB9 gene sequence. We identified a region in exon 1 where the number of mapped reads was low in numerous samples; this region matched the deletion region of HOXB9v (Figure 4).…”
Section: Identification Of a Novel Transcript Hoxb9v Which Lacksmentioning
confidence: 99%